The Role of Professional Identity in Mediating Self-Directed Learning’s Influence on Teaching Creativity - Alifa Salsabila; Muhammad Fahmi Johan Syah (South Sulawesi Education Development (SSED), 2025)
The purpose of this research is to ascertain how Professional Identity (PI) in mediating the connection between Self-Directed Learning (SDL) and Teaching Creativity (KM). A quantitative method and path analysis were employed to gather data via an online survey from 170 students enrolled in the Teacher Professional Education Program (PPG) at Muhammadiyah University of Surakarta. SDL acted as the independent variable, PI functioned as the mediator, and KM was designated as the dependent variable. The findings indicate that SDL is a strong predictor of PI (0.611, p < 0.001), and PI is a strong predictor of KM (0.697, p < 0.001). Nonetheless, once PI is incorporated into the model, the direct influence of SDL on KM turns statistically insignificant (0.073, p = 0.259), suggesting complete mediation. This indicates that SDL affects KM solely by influencing PI students with strong SDL abilities often cultivate a stronger PI, which subsequently enhances teaching creativity. These results indicate that SDL by itself is inadequate for improving KM establishing a solid professional identity is crucial. Consequently, teacher education programs must not only foster independent learning abilities but also enhance PI to promote innovative and creative teaching methods.